2017
DOI: 10.21608/ejnf.2017.104073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial or Total Inclusion of Betaine and/or Choline Instead of Added Methionine in Broiler Diets On: 2-Carcass Characteristics, Some Blood Parameters and Sensory Evaluation of Meat

Abstract: his study was carried out to investigate the effect of partial or total replacement of added DL-methionine (Met) with betaine (BET) or choline or both in diets of broiler chicks on carcass characteristics, some blood parameters and sensory evaluation of meat. A total number of four hundred and forty day-old straight-run Cobb 500 broiler chicks were randomly, weighed and divided into eleven treatments (forty birds each). Each treatment contained four replicates of ten birds. Three basal diets were formulated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Further, Waldroup et al [17] reported increased breast meat yield in broilers after choline or betaine additions at 1,000 mg/kg or 500 mg/kg. According to El-Shinnawy et al [57], adding methionine to betaine, choline, or both could improve broiler carcass yield and total edible parts yield. Betaine included in the diet at a rate of 2 g/kg increased the proportion of breast muscle and its output, according to Nutautaite et al [58].…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Further, Waldroup et al [17] reported increased breast meat yield in broilers after choline or betaine additions at 1,000 mg/kg or 500 mg/kg. According to El-Shinnawy et al [57], adding methionine to betaine, choline, or both could improve broiler carcass yield and total edible parts yield. Betaine included in the diet at a rate of 2 g/kg increased the proportion of breast muscle and its output, according to Nutautaite et al [58].…”
Section: Carcass Traitsmentioning
confidence: 99%